recreational strategies to foster the school integration of children with cancer of the pediatric hospital DR. AGUSTÍN ZUBILLAGA (Revista Electrónica REDINE, 2018)
The present work of educative innovation had like intention to offer recreational strategies to favor the scholastic integration of the children and adolescents with cancer of the University Hospital Paediatric “Dr. Agustín Zubillaga”, in Barquisimeto, Lara State. The study was framed within the qualitative paradigm of investigation, the same was developed in phases beginning by the diagnosis in which it was used for the information harvesting the techniques of participant observation and the structured interview, first it allowed to know the evolution the students in the learning atmosphere and second it collected of the mothers of the students, the educational ones of the service of the hospitable classroom and the own students; once systematized and analyzed collected, it was come to triangular it concluding that the subjects only saw the hospitable classroom like a distraction place, remaining to him importance to the academic process and therefore to the curricular content of the offered activities. Starting off of these conclusions it was elaborated and I execute a proposal that allowed to work the curricular contents that the students required of a significant way through recreational strategies, those that allowed the children to construct to knowledge from the interactions and the mediation of the educational one, facilitating its permanence in the hospitable classroom and its future scholastic integration. Managing itself also to involve to the relatives and the diverse actors who participate in the area of the health in all the raised activities, obtaining therefore a great impact in the learning atmosphere.
Keywords: recreational strategies; scholastic integration; cancer